How Should Self-Esteem Be Considered in Cancer Patients? - Niveau, Noémie; New, Boris; Beaudoin, Marine (Frontiers in Psychology, 2021)
Numerous studies showed that cancer significantly increases the risk of developing depressive and anxious symptoms. It has been shown that self-esteem is an important psychological resource and is associated with many health behaviors. Furthermore, the vulnerability model of low self-esteem, which has received strong empirical support, highlights that low self-esteem is a real risk factor in the development of depressive disorders. This article aims at providing an overview of the involvement of self-esteem in the psychological adjustment to cancer. After briefly reviewing the literature, we suggest that its implication in the development of depressive disorders and its association with coping strategies and social support in cancer patients justify the consideration of self-esteem in oncology psychological care, especially in young adult patients and those with significant physical impairment following treatment.